Forming the integrality in health concept based on the historical-cultural approach - Rosangela Andrade Aukar de Camargo; Fabiana Maria das Graças Corsi Zuelli; Adrielle Naiara Toneti; Marta Angélica Iossi Silva; Marlene Fagundes Carvalho Gonçalves; Luciane Sá de Andrade (Universidade Federal de Goias, 2015)
This study analyzed the formation of the concept integrality in health by undergraduate students of the nursing bachelor and licensure course in a historical-cultural approach. This is a qualitative descriptive study, conducted in a public state university, with 24 students. The information was collected through interviews and it generated three categories agreeing with the stages to form a scientific concept, entitled: The initial plurality of the integrality in health concept senses; From generalizations of subjective impressions to concreate attributes; The potential concept or pseudo-concept. The analysis revealed a dialectic process between thoughts and speech. The integrality in health concept evolved from the words "everything" and "whole", to an association with the Unified Health System principle, to the team work as guide for health practices and organization of services. It is concluded that the formation theory of concepts in the historical-cultural approach, allowed to identify advances and gaps in learning when building knowledge of students.